PENGARUH KOMPETENSI, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA BINTARA DINAS OPERASI PANGKALAN TNI ANGKATAN UDARA SULTAN HASANUDDIN - S, Wanda; Dirwan, A (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2024)
The Indonesian Air Force faces complex challenges with technological advances and changing times. The operations service non-commissioned officer at Sultan Hasanuddin Air Force Base, Makassar, is responsible for supporting flight operations. However, in reality, the performance of personnel, especially the operations service non-commissioned officers, in carrying out their duties did not show the results expected by the Indonesian Air Force. Some non-commissioned officers do not meet organizational competencies, do not have a conducive work environment to increase motivation, and lack discipline in implementing the rules. These three variables influence their performance. This research aims to analyze the influence of competency, work environment and work discipline on the performance of non-commissioned officers at the Sultan Hasanuddin Air Force Base Operations Service. This research uses a quantitative approach, survey methods and path analysis. The population was 70 people, with a saturated sampling technique, 70 respondents were obtained, consisting of 20 people for the instrument test and 50 people for the research test. The data was processed and analyzed using Excel and SPSS version The research results showed that: Competence had a direct positive and significant effect on work discipline of 0.359; The work environment has a direct positive and significant effect on work discipline of 0.566; Competency has a direct positive and significant effect on performance of 0.427; The work environment has a direct positive andsignificant effect on performance of 0.405; Work discipline has a direct positive and significant effect on the performance of the Non-Commissioned Officer of the Sultan Hasanuddin Air Force Base Operations Service by 0.253.